A Large, Finite Permutation of Specific, Discrete Variants: Dan Graham's Children's Pavilion at Chambres d'Amis (1986). (3rd July 2021) - Van Gerrewey, Christophe
Summary: In 1986, Dan Graham participated in Chambres d'Amis in Ghent, Belgium, curated by Jan Hoet as an art exhibition outside of the museum, in individual houses. With the help of a local architect, Graham constructed a glass and steel pavilion in a private garden. The resulting work, Children's Pavilion, is largely forgotten, but it is a pivotal work within the evolution of his oeuvre. Many of Graham's concerns and topics – such as the relationship between public and private, the nature of a garden, and the possibility of site-specific art works, closer to architecture than to the fine arts, outside of the museum – were also an important part of the exhibition concept of Jan Hoet. Moreover, Children's Pavilion is not a 'unique' work: it is closely related to previous works (both pavilions and spatial proposals), while it has also spawned – and continues to spawn – new projects, collaborations (with Jeff Wall) and pavilions that are often seemingly identical. This double proliferation – both topological and permutational in nature – is typical for his oeuvre, but it also creates very specific problems. Everything within his body of work seems connected, and although these connections are necessary to fully understand each individual pavilion or proposal, they are in many cases still waiting to be revealed.